Drosophila Caliban preserves intestinal homeostasis and lifespan through regulating mitochondrial dynamics and redox state in enterocytes. - Dai, Z.; Li, D.; Du, X.; Ge, Y.; Hursh, D.A.; Bi, X. (PLoS Genetics, 2020)
Precise regulation of stem cell activity is crucial for tissue homeostasis. In Drosophila, intestinal stem cells (ISCs) maintain the midgut epithelium and respond to oxidative challenges. However, the connection between intestinal homeostasis and redox signaling remains obscure. Here we find that Caliban (Clbn) functions as a regulator of mitochondrial dynamics in enterocytes (ECs) and is required for intestinal homeostasis. The clbn knock-out flies have a shortened lifespan and lose the intestinal homeostasis. Clbn is highly expressed and localizes to the outer membrane of mitochondria in ECs. Mechanically, Clbn mediates mitochondrial dynamics in ECs and removal of clbn leads to mitochondrial fragmentation, accumulation of reactive oxygen species, ECs damage, activation of JNK and JAK-STAT signaling pathways. Moreover, multiple mitochondria-related genes are differentially expressed between wild-type and clbn mutated flies by a whole-genome transcriptional profiling. Furthermore, loss of clbn promotes tumor growth in gut generated by activated Ras in intestinal progenitor cells. Our findings reveal an EC-specific function of Clbn in regulating mitochondrial dynamics, and provide new insight into the functional link among mitochondrial redox modulation, tissue homeostasis and longevity.